Core–Shell Crystals of Porous Organic Cages. (10th June 2018) - Jiang, Shan; Du, Yi; Marcello, Marco; Corcoran, Edward W.; Calabro, David C.; Chong, Samantha Y.; Chen, Linjiang; Clowes, Rob; Hasell, Tom; Cooper, Andrew I.
Abstract: The first examples of core–shell porous molecular crystals are described. The physical properties of the core–shell crystals, such as surface hydrophobicity, CO2 /CH4 selectivity, are controlled by the chemical composition of the shell. This shows that porous core–shell molecular crystals can exhibit synergistic properties that out‐perform materials built from the individual, constituent molecules.